(untitled) (Globalization and Business, 2023)
What does the Balance of Payments deficit mean? The deficit of the balance of payments does not always mean economic downturn, or vice versa. However, achieving and maintaining the balance of international economic relations is an important macroeconomic task for any country. In this regard, the in-depth analysis of the balance of payments tendencies is extremely important, especially for Georgia. Unfortunately, in our country often approaches and methods of analysis are inadequate, communication with users is delayed, data transparency is insufficient, academic circles are less interested in external sector statistics problem. The purpose of this paper is to provoke designing of comprehensive foreign sector data analysis among appropriate specialists.